Daemonorops draco Blume Induces Apoptosis Against Acute Myeloid Leukemia Cells via Regulation of the miR-216b/c-Jun - Park, Moon Nyeo; Jeon, Hee Won; Rahman, Md. Ataur; Park, Se Sun; Jeong, Se Yun; Kim, Ki Hyun; Kim, Sung-Hoon; Kim, Woojin; Kim, Bonglee (Frontiers in Oncology, 2022)
Daemonorops draco Blume (DD), also called dragon's blood, has been used as a traditional Korean medicine especially for analgesic due to wound infection. Recently, the effect of DD was identified in relation with anti-bacterial and anti-analgesic efficacies. In this study, the underlying anti-cancer effect was investigated in associated with apoptosis in U937 (acute myeloid leukemia cell) and THP-1 (acute myeloid leukemia cell). DD exhibited cytotoxic effect and induced apoptosis in U937 and THP-1 cells. Conversely, depletion of mitochondrial membrane potential (ΔΨ) (MMP) decreased by DD treatment. The protein expression of cleaved Poly (ADP-ribose) polymerase (PARP), cleaved caspase-3, p-H2A.X, CCAAT/enhancer-binding protein-homologous protein (CHOP) and activating transcription factor 4 (ATF4) were upregulated by DD treatment. Consistently, DD treated cells elevated reactive oxygen species (ROS) generation in a concentration dependent manner via miR-216b activation in association with inhibition of c-Jun. N-acetyl-L-cysteine (NAC) pretreatment was found to reverse cytotoxic effect and ROS generation by DD treatment. Additionally, the expression of miR-216b was increased by DD treatment in a dose-dependent manner. Collectively, our study suggestes that anti-cancer effect of DD subsequently promoted CHOP-dependent apoptosis along with ROS generation via upregulation of miR-216b against acute myeloid leukemia.